An Unusual Presentation of Jejunal Stenosis: A Case Report - Elkheir, Ibrahim Salih; Salman, Diaa eldinn Yaseen; Nugud, Faisal Abdelgalil; A, Suha Tawfiq; A, Ali Hamad (Gezira Journal of Health Sciences, 2013)
Late presentation of jejunal atresia or stenosis is very rare. All patients present within the 1 st to 5 th day of life. They present with symptoms and signs of intestinal obstruction. Bilious vomiting is one of the most important and diagnostic feature. Other symptoms and signs of intestinal obstruction are very rare. In patients with duodenal stenosis the presentation is usually late and their main presenting symptom is failure to thrive with or without symptoms of intestinal obstruction. Here we present a thirty one month female who was seen with symptoms and signs of chronic intestinal obstruction. Her main symptoms were bilious vomiting, abdominal distension and constipation. The condition started since birth. Pregnancy was uneventful and she was an outcome of spontaneous vaginal delivery with birth weight of 3kg.